Mediated city. Experience, daily life and the representation of Rio de Janeiro on social networks - Rezende, Renata (2016)
This paper aims to discuss how, in contemporary, everyday life in the city is crossed by the cyberspace, which ushered in new flows, affections and allegories, particularly with the advent of digital social networks. In this cut, we question how narratives about the city of Rio de Janeiro on the social network Facebook publicize relationships they establish tuned sense of production to the company’s characteristics in network, where the paradox of mobility is configured in conjunction with the mediated representation of space and experience of urban life.